The influence of music environment on conceptual design creativity - Xia, Tiansheng; Sun, Yongqing; An, Yi; Li, Linli (Frontiers in Psychology, 2023)
Creativity plays an important role in design. However, there have been mixed results with regard to whether music, as an environmental stimulus, improves design creativity performance. Participants were 57 design major students who were randomly assigned to one of three groups, with 19 students in each group: no music, pure music, and music with intelligible semantic information (unrelated to the task) playing in the background. Each participant completed a design task (design a tool for storing painting materials), with two phases in it, one that involved idea generation (divergent thinking) and one that involved idea evaluation (convergent thinking). Performance in the two phases was rated based on six indices of creativity (fluency; flexibility; adaptability; feasibility; usefulness; novelty) and overall design creativity (ODC). The results of one-way ANOVAs with Bonferroni correction showed that neither music environment had a significant influence on divergent thinking in idea generation or convergent thinking in idea evaluation. However, both music environments had a significantly positive effect on novelty and ODC. We discuss the implications of our current results for fostering designers’ creativity performance.